2016
DOI: 10.3906/vet-1508-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of DGAT1 polymorphism on milk production traits in dairycows depending on environmental temperature

Abstract: Heat stress is a growing problem in dairy cattle breeding because of global warming and because of the genetic selection for greater production that reduces thermotolerance in cows. The negative influence of elevated environmental temperatures on economically important traits is well recognized in cattle. Thermal stress is responsible for decreased milk yield, milk fat, and protein contents, as well as reduced dry matter intake, health, and fertility (1,2). According to Gorniak et al. (2), even mild heat stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The high proportion of the lysine variant K232 observed in the current study might contribute to the higher fat content in native cattle in Ethiopia and other Bos indicus breeds than in HF cross cattle. The frequency of the lysine variant K232 in the investigated Boran * HF cross cattle is similar to that found in studies of other HF populations or their crosses, which have reported a range from 0.21 to 0.63 (Ahani et al, 2015;Akyüz et al, 2015;Komisarek and Kolenda, 2016;Bhat et al, 2017;Li et al, 2020;Krovvidi et al, 2021). The differences in the frequency of the lysine variant K232 among breeds might result from different breeding goals and the considerable Holstein contribution to the blood level of Boran * HF cross cattle.…”
Section: Allele and Genotype Frequencies Of The K232a Protein Variantsupporting
confidence: 86%
“…The high proportion of the lysine variant K232 observed in the current study might contribute to the higher fat content in native cattle in Ethiopia and other Bos indicus breeds than in HF cross cattle. The frequency of the lysine variant K232 in the investigated Boran * HF cross cattle is similar to that found in studies of other HF populations or their crosses, which have reported a range from 0.21 to 0.63 (Ahani et al, 2015;Akyüz et al, 2015;Komisarek and Kolenda, 2016;Bhat et al, 2017;Li et al, 2020;Krovvidi et al, 2021). The differences in the frequency of the lysine variant K232 among breeds might result from different breeding goals and the considerable Holstein contribution to the blood level of Boran * HF cross cattle.…”
Section: Allele and Genotype Frequencies Of The K232a Protein Variantsupporting
confidence: 86%
“…However, some of the milk production traits (milk protein yield and milk yield) were not constant throughout the lactation and slightly decreased with change in environmental temperature (20-28 • C). The more prominent effect of DGAT K232A in Polish Holstein-Friesian was not observed because the temperature was moderate (5 • C−28 • C) in this study (75). Shahzad et al noticed the low hepatic expression of DGAT1 in periparturient dairy cattle during summer compared with spring (76).…”
Section: Dgat1 K232a Association With Milk Production In Cattlementioning
confidence: 49%
“…Environmental conditions, such as season, nutrition, and management, are also variables that can modify gene expression of most of the traits of interest. Recently, studies revealed that polymorphisms in diacylglycerol O-acyltransferase 1 (DGAT1) and stearoyl-CoA desaturase 1 (SCD1) genes showed different effects on milk production traits and fatty acid (FA) composition according to the season and temperature (Duchemin et al, 2013;Komisarek and Kolenda, 2016). In addition, a joint GWAS of the Chinese and Danish Holstein populations showed potential genotype by environment Genome-wide association study for milk production traits in a Brazilian Holstein population interaction for milk FA traits (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%